Karakteristik Kepemimpinan Pendidikan di Pesantren - Sri Wahyuni; Inom Nasution (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Leadership is the main functional element in management because the aim of management is to manage and mobilize, organize and make decisions on the existing resources of the Islamic boarding school. For the success of leadership, a leader must walk on the trust of his members, because a leader is the captain in the world of education. As a captain, a leader must be able to prove to his members that he can be trusted because leadership success is not the result of individual work but the result of competent collaborative work. The aim of this research is to understand more deeply the characteristics that must exist in a leader so that the leader can play his role optimally and the educational program can be successful. This research uses a literature study method in the form of several leadership journals and books. The results of this research show that after understanding the characteristics of an ideal leader, it should be adjusted to the leadership model that will be chosen. All attitudes and behavior of a leader must be able to build trust and confidence with his subordinates, because leaders are the bridge to achieving the mission of the Islamic boarding school.